A STUDY ON HYDRO-MORPHODYNAMIC BEHAVIOUR OF THE KIRTANKHOLA RIVER USING DELFT3D MODEL - RAHMAN, NOMAN; SADIA, NUZHAT FARHAT (My University, 2024)
The Kirtankhola River is a meandering river in Bangladesh's southern region where the second-largest river port in the country is situated. It has a tendency to erode and its flow contains huge amounts of sediment. In order to identify the hydrodynamic alterations and related morphological changes of the Kirtankhola River, a hydromorphological study of the river is essential. In this study, hydrodynamic and morphological behaviour of Kirtankhola River is assessed by developing a two - dimensional model using Delft3D and Image Analysis using ArcGIS respectively. The selected reach for developing the Delft3D model is approximately 19.2 km from the downstream of Arial Khan River (u/s) to Barishal Launch Ghat (d/s). The model is calibrated against the observed water level at Barishal Launch Ghat for the months of June-September, 2010. Then it is validated at the same place for the months of June-September, 2022. After calibration and validation, the model is simulated for both of the years and used to study the hydrodynamic and morphological behaviour of the study area. Following that, an assessment is made of the morphological features, including quantification of bed shear stress and critical shear stress. In order to conduct image analysis of the study area, we obtained Landsat images spanning 23 years, divided into 3-year intervals: 2000, 2003, 2006, 2009, 2012, 2015, 2018, 2021, 2023. All the images have been downloaded from USGS EarthExplorer. The findings from the image analysis indicate significant accretion and erosion in different regions, with accretion facilitating Chars' growth while erosion contributes to bank shifting. Erosion occurs annually, with 2009 being the most significant. Area-1(at Char Monai near At Hazar) experienced significant accretion, while Area-2(opposite bank of Char Baria Riverside) experienced erosion, surpassing accretion by nearly fourfold. Major erosion occurred in 2012-2015 in Area-2. The bed shear stress data from 2010 and 2022 was analyzed using five observation points on the Delft3D model. In 2010, the maximum stress was 0.5377 N/m2 , and the average shear stress was 0.3277 N/m2 . In 2022, the maximum stress was 0.9315 N/m2 , and the average shear stress was 0.7603 N/m2 . The critical shear stress was 0.185 N/m2 . It is evident from the model that the maximum and average bed shear stress exceeded the critical shear stress, indicating erosion is occurring. However, some contradictions between the outputs of the ArcGIS study and the Delft3D model were found due to the inadequacy of the required data. Apart from all the limitations, we hope our findings from this assessment will be helpful to understand the overall hydro-morphodynamic behaviour of the river and suggest possible future development works to be implemented on this river through further modifications.
A Study On Hydro-Morphodynamic Behaviour of The Kirtankhola River Using Delft3D Mode